Foreign Policy Making and the American Political System - NATHAN, James A (Little Brown and Company, 1983)
Unlike other books on U.S. foreign policy making, this highly regarded text by James Nathan and James Oliver focuses on the institutional context of policy making and the processes that take place within it. This thoroughly revised third edition takes particular note of the events that have shaped the world and U.S. foreign policy since 1989.